A Study on the Ideal Amount of Extensive Reading for High Schools in Japan - Tekka Chang; Christine Dineros (Beyond Words, 2022)
Abstract     When introducing extensive reading, I always had a difficult time in getting everyone to be contented. Starting with the Oxford Bookworms, I prepared over 500 books in the school library in both fiction and non-fiction books. Vocabulary level tests were also conducted to make sure that the books were at the I+1 level, and the author talked to each student to see which genre they may like. While this is a difficult task, I tried to find the ideal amount of weekly reading for science course students in a senior high school in Japan. A quantitative questionnaire was created using the price sensitivity meter method to measure the learners’ ideal weekly reading amount. Results showed that the ideal amount of weekly extensive reading was 1200 words per week at the 500-word level. When asked directly about the amount of ideal reading according to their level, 44% of the students said that reading 2000 words per week was “little or no problem”.